2019
DOI: 10.2478/afepuc-2019-0013
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of High-Intensity Exercise on Changes of Blood Concentration Components in Algerian National Judo Athletes

Abstract: Summary The aim of the present study to verify the impact of judo competition on changes in the blood count of judo athletes during an official competition. Also to compare these results with the different weight category. Methods: fifteen youth trained athletes were included in the study were divided into three groups according to weight category (light, medial, and heavy) weight. All subjects performed a 5×4mn round of competition with 15mn of rest between rounds and Complete Blood Count (CBC) were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…there are a considering changes in level indicators development of the maximum dynamic force of abdominal muscles the press, found mainly a significant improvement, both Men and women of the main groups, and these differences statistically significant (p <0,001). The above is confirmed by the data of [9; 13; 16], according to which it was found that during physical exertion, muscle hypertrophy occurs as a result of adaptivetrophic influence [7], which is characterized by an increase in thickness and denser packaging of contractile elements of muscle fiber. Thus, studies [24] indicate that the introduction of functional exercises in the main part of the lesson contributed to a significant improvement in strength abilities of high school students.…”
Section: Discussionsupporting
confidence: 67%
“…there are a considering changes in level indicators development of the maximum dynamic force of abdominal muscles the press, found mainly a significant improvement, both Men and women of the main groups, and these differences statistically significant (p <0,001). The above is confirmed by the data of [9; 13; 16], according to which it was found that during physical exertion, muscle hypertrophy occurs as a result of adaptivetrophic influence [7], which is characterized by an increase in thickness and denser packaging of contractile elements of muscle fiber. Thus, studies [24] indicate that the introduction of functional exercises in the main part of the lesson contributed to a significant improvement in strength abilities of high school students.…”
Section: Discussionsupporting
confidence: 67%
“…there are a considering changes in level indicators development of the maximum dynamic force of abdominal muscles the press, found mainly a significant improvement, both Men and women of the main groups, and these differences statistically significant (p <0.001). The above is confirmed by the data of (Adel et al, 2019;Mokhtar et al, 2019;Saddek et al, 2020), according to which it was found that during physical exertion, muscle hypertrophy occurs as a result of adaptive-trophic influence (Mukund & Subramaniam, 2020;Teplov, 1982), which is characterized by an increase in thickness and denser packaging of contractile elements of muscle fiber (Haun et al, 2019;Narici et al, 1996). Thus, studies (Annesi, Westcott, Faigenbaum, & Unruh, 2005;Belkadi et al, 2019;Krivoruchko et al, 2018;I.…”
Section: Discussionmentioning
confidence: 60%
“…However, according to the results of a number of authors (Adel, Alia, & Mohammed, 2020;Andrieieva et al, 2020;Bodnar & Andres, 2016;Krivoruchko et al, 2018;Palichuk et al, 2018;Prysiazhniuk et al, 2021;Sibley, 2012), currently operating lessons are ineffective, monotonous, do not sufficiently stimulate students to physical culture and sports activities. Therefore, this problem requires the search for new interesting forms, innovative means, methods and principles of system improvement physical education, increasing the volume and diversification of types of motor activity (Adel et al, 2019;Cacioppo et al, 2021;Petrova & Bala, 2020;Pricop, A. D., Pelin, R., Florescu, O., & Mezei, M. D., 2020;Voloshina et al, 2018). A number of scientists pay considerable attention to the issue optimization of the content of physical education lessons (I.…”
Section: Introductionmentioning
confidence: 99%
“…In possession of the data from the training and competition videos, it was possible to cross them to obtain a percentage quantification of the use of each type of handgrip, for each athlete, in the dominant and non-dominant hand. The analysis of the training videos was supervised by an expert (Adel et al, 2019) in affordance and hand-object interaction. To measure handgrip strength, two dynamometers were used, developed at the Instrumentation Laboratory (Adel et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The analysis of the training videos was supervised by an expert (Adel et al, 2019) in affordance and hand-object interaction. To measure handgrip strength, two dynamometers were used, developed at the Instrumentation Laboratory (Adel et al, 2019). The measurement of the palm gripping force was performed by means of a "ring" load cell, and the gripper grip force by means of an "S" load cell.…”
Section: Methodsmentioning
confidence: 99%